Elevated monocyte HLA-DR in pediatric secondary hemophagocytic lymphohistiocytosis: a retrospective study - Raimbault, Sylvain; Monneret, Guillaume; Gossez, Morgane; Venet, Fabienne; Belot, Alexandre; Zekre, Franck; Remy, Solene; Javouhey, Etienne (Frontiers in Immunology, 2023)
Introduction Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening condition, and its diagnosis may be challenging. In particular, some cases show close similarities to sepsis (fever, organ failure, and high ferritin), but their treatment, while urgent, differ: prompt broad-spectrum antibiotherapy for sepsis and immunosuppressive treatment for HLH. We questioned whether monocyte human leucocyte antigen (mHLA)–DR could be a diagnostic marker for secondary HLH (sHLH). Methods We retrospectively reviewed data from patients with a sHLH diagnosis and mHLA-DR quantification. mHLA-DR data from healthy children and children with septic shock, whose HLA-DR expression is reduced, from a previously published study were also included for comparison. Results Six patients with sHLH had mHLA-DR quantification. The median level of monocyte mHLA-DR expression in patients with sHLH [79,409 antibodies bound per cell (AB/C), interquartile range (IQR) (75,734–86,453)] was significantly higher than that in healthy children and those with septic shock (29,668 AB/C, IQR (24,335–39,199), and 7,493 AB/C, IQR (3,758–14,659), respectively). Each patient with sHLH had a mHLA-DR higher than our laboratory normal values. Four patients had a second mHLA-DR sampling 2 to 4 days after the initial analysis and treatment initiation with high-dose corticosteroids; for all patients, mHLA-DR decreased to within or close to the normal range. One patient with systemic juvenile idiopathic arthritis had repeated mHLA-DR measurements over a 200-day period during which she underwent four HLH episodes. mHLA-DR increased during relapses and normalized after treatment incrementation. Conclusion In this small series, mHLA-DR was systematically elevated in patients with sHLH. Elevated mHLA-DR could contribute to sHLH diagnosis and help earlier distinction with septic shock.